The adventures of Ibn Battuta - Mohd. Asraf, Ratnawati (Budaya Ilmu Sdn Bhd, 1993)
The story you are about to read is a true story about a famous traveler named Ibn Batutta. Ibn Batutta lived about four hundred years ago and travelled to a great many countries. You will read about the place he visited. Some of the places no longer exist, while others still do. You will also read about how people lived during those times. You will see what things were important to them, how they behaved, and how they felt, it will be interesting to compare how things in these countries may have changed or how they have remained the same. As you read the book, you will also find out about the things that are important to Ibn Batutta. You will find that Ibn Batutta spent a lot of time describing the scholars that he met. This is because Ibn Batutta had a love for knowledge. In fact, the main purpose of his travelling was the pursuit of knowledge. He wanted to seek knowledge because the seeking of knowledge is very important in Islam; it is the duty of every Muslim man and every Muslim woman to seek knowledge.